Importancia de la valoración del testimonio de la víctima como único testigo en el delito de violación a la luz de la normativa ecuatoriana - Ruiz Estrella, Deisi Marisol (2024)
In Ecuador, the crime of rape is one of the most common crimes committed, and according to doctrine, these typical unlawful and culpable acts are usually committed clandestinely, which is why prior testimony is of great value to the justice system. However, there are situations in which the prosecution relies solely on the testimony of the victim, or presents all the evidence relevant to the case, but it is not effective. In such cases, the victim becomes the only witness. In this sense, the objective of this study was to find out how the victim's testimony is valued as the only witness in the crime of rape in the light of Ecuadorian law, through national and international norms, in order to determine the criteria used by the judge to determine the criminal responsibility of the accused. For the elaboration of this research, the qualitative approach was used because it was a documentary research, focused on the descriptive level of depth, in this sense the methods used were normative and analytical, the techniques applied were documentary and interview, this allowed to receive direct information provided by the professionals interviewed, the use of non-probabilistic sampling helped to select four people who were within reach of the interviewer such as: a prosecutor, two judges of the Criminal Court of Imbabura, and a criminal lawyer. The results showed that the victim's testimony alone is not sufficient to determine the criminal responsibility of the accused, because Ecuadorian jurisprudence states that carnal access must be proven by expert evidence, i.e., with a forensic medical examination.